Atomically Substitutional Engineering of Transition Metal Dichalcogenide Layers for Enhancing Tailored Properties and Superior Applications - Liu, Zhaosu; Tee, Si Yin; Guan, Guijian; Han, Ming‑Yong (Nano-Micro Letters, 2024)
Transition metal dichalcogenides (TMDs) are a promising class of layered materials in the post-graphene era, with extensive research attention due to their diverse alternative elements and fascinating semiconductor behavior. Binary MX2 layers with different metal and/or chalcogen elements have similar structural parameters but varied optoelectronic properties, providing opportunities for atomically substitutional engineering via partial alteration of metal or/and chalcogenide atoms to produce ternary or quaternary TMDs. The resulting multinary TMD layers still maintain structural integrity and homogeneity while achieving tunable (opto)electronic properties across a full range of composition with arbitrary ratios of introduced metal or chalcogen to original counterparts (0–100%). Atomic substitution in TMD layers offers new adjustable degrees of freedom for tailoring crystal phase, band alignment/structure, carrier density, and surface reactive activity, enabling novel and promising applications. This review comprehensively elaborates on atomically substitutional engineering in TMD layers, including theoretical foundations, synthetic strategies, tailored properties, and superior applications. The emerging type of ternary TMDs, Janus TMDs, is presented specifically to highlight their typical compounds, fabrication methods, and potential applications. Finally, opportunities and challenges for further development of multinary TMDs are envisioned to expedite the evolution of this pivotal field. Highlights: 1 Atomically substitutional engineering in binary transition metal dichalcogenides (TMDs) enables the facile production of ternary or quaternary TMDs with tunable (opto)electronic properties spanning the entire compositional spectrum. 2 A comprehensive overview is provided on multinary TMDs, including Janus-type structures, aiming to elaborate on their theoretical foundations, synthetic strategies, tailored properties, and superior applications. 3 The challenges and opportunities faced in accelerating the exploitation of multinary TMDs as highly promising nanomaterials are discussed.